Perspective on the role of norms for institutional behavior and policy design in European cross-border regions - Svensson, Sara (Frontiers in Sociology, 2025)
The article analyses how a norm scientific perspective can advance our understanding of cross-border regions and guide future directions of research. Cross-border regions are territorial spaces comprising territory from two or more national states, located directly at the borders of those spaces. Since the 1950s it has become increasingly common that cross-border organizations, constituted by local municipalities and regional authorities and sometimes private entities, are established to coordinate governance processes around shared policy problems. These organizations fit into a Type II model of European multi-level governance as complex, fluid, and carried out in overlapping jurisdictions. A norm scientific perspective focuses on joint expectations as a primary predictor of behavior and thereby on social structures as well as social transformations. In accordance with institutional theory, norms are understood as intersubjective, widely shared, but often implicit, expectations and rules that guide human behavior. The article makes two arguments. First, it argues that a norm-scientific perspective has the potential to significantly advance the scientific community's understanding of various aspects related to how cross-border cooperation emergence and functioning. Second, it argues that cross-border regions constitute a promising venue to advance the knowledge of how norms can be studied and understood.